Optimization and activation of renewable durian husk for biosorption of lead(II) from an aqueous medium - Ngabura, Mohammed; Hussain, Siti Aslina; Ab Karim Ghani, Wan Azlina; Jami, Mohammed Saedi; Tan, Yen Ping (John Wiley and Sons Ltd, 2019)
BACKGROUND:BiosorptionofleadPb(II)bydurianhuskactivatedcarbon(DHAC)wasinvestigated.Themainaimofthisworkis toexploretheeﬀectofoperatingvariablessuchaspH,biosorbentdose,temperature,initialmetalionconcentrationandcontact time on the removal of Pb(II) from synthesized aqueous medium using a response surface methodology (RSM) technique. The experimentationwasperformedintwosets,namelyset1andset2. RESULTS:Forexperimentalset1,pHwassetto7.0.Theoptimumconditionsfortheremainingparametersweredeterminedtobe 0.39gDHACdose,60mincontacttimeand100mgL−1 ofinitialmetalionconcentration,whichyieldedmaximumbiosorption capacity of 14.6mgg−1. For experimental set 2, 41.27∘C, 8.95 and 99.96mgL−1 were the optimum conditions determined for temperature, pH and initial Pb(II) concentration, respectively; which revealed a maximum adsorption capacity of 9.67mgg−1. Characterizationoftheadsorbentrevealedactivefunctionalgroupssuchashydroxyl,carboxylic,alcoholandhemicellulose.The equilibriumadsorptiondataobeyedtheLangmuirisothermandpseudo-second-orderkineticmodelswithmaximumLangmuir uptakeof36.1mgg−1. CONCLUSIONS: The biosorbent was capable of reuse, so that the abundant durian husk could be utilized eﬀectively for the removalofPb(II)frompollutedwater.